Trends of Postpartum Haemorrhage and Its Management in Tertiary Care Hospital, Bangladesh (Sir Salimullah Medical College Journal, 2026)
Background: Postpartum hemorrhage (PPH) is the leading cause of maternal mortality globally, accounting for nearly 25% of maternal deaths. In low-resource settings, it contributes to almost half of all postpartum fatalities, highlighting the urgent need for early identification and effective management. The aim of the study is to evaluate the clinical and demographic profile of patients experiencing postpartum hemorrhage (PPH) and to identify associated risk factors. Methods: This prospective observational study was conducted over six months (July 2022 to December 2022) in the Department of Obstetrics and Gynaecology at Sir Salimullah Medical College Mitford Hospital, Dhaka. All patients admitted with postpartum hemorrhage (PPH), or who developed PPH after vaginal delivery or cesarean section within the hospital, were included. PPH was defined as blood loss exceeding 500 mL after vaginal delivery or 1,000 mL after cesarean section, or any postpartum bleeding leading to clinical shock, transfusion, or surgical intervention. Data were collected using a structured checklist and analyzed using SPSS. Results: Out of 1,845 deliveries during the study period, 189 cases (10.24%) of postpartum hemorrhage (PPH) were identified 109 patients were referred from outside the hospital, while 80 developed PPH in-hospital. Among in-hospital deliveries, the incidence of PPH was 6.26%, despite active management of the third stage of labor. The leading causes were retained placenta with uterine atony (70.69%), genital tract injury (14.68%), uterine atony alone (8.25%), morbidly adherent placenta (5.46%), and uterine inversion (0.92%). Most patients were over 35 years of age, with a mean monthly family income of 4,200 Tk. Multiparity was seen in 61.90%, and 75.13% had received antenatal care; however, 60.85% had no identifiable risk factors. Notably, 84.40% of cases delivered by untrained birth attendants. On admission, 57.67% were in shock. Management included manual removal of placenta (44.37%), genital tract repair (13.76%), uterine vessel ligation (6.08%), condom tamponade (4.23%), and hysterectomy (5.82%). The overall recovery rate was 98.94%; one patient (0.53%) developed Sheehan’s syndrome, and one (0.53%) died. Conclusion: PPH was more common among older, multiparous, and low-income women, with many cases occurring without identifiable risk factors. Active management of the third stage of labor and prompt interventions markedly reduced complications and improved outcomes, emphasizing the need for skilled attendance and timely care.Sir Salimullah Med Coll J 2025; 33: 53-60